Regions with low rates of bystander cardiopulmonary resuscitation (CPR) have lower rates of CPR training in Victoria, Australia - Bray, Janet; Straney, L.; Smith, K.; Cartledge, S.; Case, R.; Bernard, S.; Finn, Judith (Wiley-Blackwell, 2017)
© 2017 The Authors. Background-Bystander cardiopulmonary resuscitation (CPR) more than doubles the chance of surviving an out-of-hospital cardiac arrest. Recent data have shown considerable regional variation in bystander CPR rates across the Australian state of Victoria. This study aims to determine whether there is associated regional variation in rates of CPR training and willingness to perform CPR in these communities. Methods and Results-We categorized each Victorian po stcode as either a low or high bystander CPR region using data on adult, bystander-witnessed, out-of-hospital cardiac arrests of presumed cardiac etiology (n=7175) from the Victorian Ambulance Cardiac Arrest Registry. We then surveyed adult Victorians (n=404) and compared CPR training data of the respondents from low and high bystander CPR regions. Of the 404 adults surveyed, 223 (55%) resided in regions with low bystander CPR. Compared with respondents from high bystander CPR regions, respondents residing in regions with low bystander CPR had lower rates of CPR training (62% versus 75%, P=0.009) and lower self-ratings for their overall knowledge of CPR (76% versus 84%, P=0.04). There were no differences between the regions in their reasons for not having undergone CPR training or in their willingness to perform CPR. Rates of survival for bystander-witnessed, out-of-hospital cardiac arrests were significantly lower in low bystander CPR regions (15.7% versus 17.0%, P < 0.001). Conclusions-This study found lower rates of CPR training and lower survival in regions with lower rates of bystander CPR in Victoria, Australia. Targeting these regions with CPR training programs may improve bystander CPR rates and out-of-hospital cardiac arrest outcomes.